Role of Psychiatry in Individuals with Gender and Sexual Variance - Uttam C. Garg (Indian Journal of Social Psychiatry, 2025)
Psychiatry is perhaps a branch of medicine that has been intricately linked with prevailing societal norms and sentiments. Historically, this has led to bias and arguably, poorer engagement with LGBTQIA+ community. Fortunately, the future outlook appears brighter as the positive trends in depathologising variance behaviours and increasing recognition among the mental health fraternity about our roles, and lack thereof in certain cases, has brought psychiatry more in line with humanistic and ethical goals. More work needs to be done however, and we must continuously strive to learn and modify our attitudes to help individuals with gender and sexual variances where needed.